A SOX5 gene variant as a possible contributor to short stature. (29th December 2020) - Gkirgkinoudis, Athanasios; Tatsi, Christina; DeWard, Stephanie J; Friedman, Bethany; Faucz, Fabio R; Stratakis, Constantine A
Abstract : Summary: SOX5 plays an important role in chondrogenesis and chondrocyte differentiation. SOX5 defects in humans (often deletions) result in a Lamb-Shaffer syndrome (LSS), presenting with speech delay, behavioral problems and minor dysmorphic features. We present a patient with idiopathic short stature (ISS) who carried a heterozygous novel variant in SOX5 . The patient had no dysmorphic features, but a skeletal survey revealed minor skeletal abnormalities. Laboratory and endocrine evaluation for known causes of growth disorders was negative. The missense variant in SOX5 gene (c.1783A>G, p.K595E) was de novo and was predicted to be deleterious by in silico programs. In summary, we present a patient whose presentation may provide evidence that gene defects in SOX5 may contribute to the etiology of short stature and/or mild skeletal defects beyond LSS. Learning points: We report a girl with idiopathic short stature and mild skeletal defects presenting with a de novo variant in SOX5 gene, predicted in silico to be deleterious. Although SOX5 has not been previously specifically associated with short stature, several evidences support its contributing effect on dyschondrogenesis. Missense variants in SOX5 gene may lead to mild phenotypes, differing from typical presentation of patients with Lamb-Shaffer syndrome.